The role of acute and chronic respiratory colonization and infections in the pathogenesis of COPD - Leung, Janice M. (2017)
COPD is a major global concern, increasingly so in the context of ageing populations. The role of infections in disease pathogenesis and progression is known to be important, yet the mechanisms involved remain to be fully elucidated. While COPD pathogens such as Haemophilus influenzae, Moraxella catarrhalis and Streptococcus pneumoniae are strongly associated with acute exacerbations of COPD (AECOPD), the clinical relevance of these pathogens in stable COPD patients remains unclear. Immune responses in stable and colonized COPD patients are comparable to those detected in AECOPD, supporting a role for chronic colonization in COPD pathogenesis through perpetuation of deleterious immune responses. Advances in molecular diagnostics and metagenomics now allow the assessment of microbe-COPD interactions with unprecedented personalization and precision, revealing changes in microbiota associated with the COPD disease state. As microbial changes associated with AECOPD, disease severity and therapeutic intervention become apparent, a renewed focus has been placed on the microbiology of COPD and the characterization of the lung microbiome in both its acute and chronic states. Characterization of bacterial, viral and fungal microbiota as part of the lung microbiome has the potential to reveal previously unrecognized prognostic markers of COPD that predict disease outcome or infection susceptibility. Addressing such knowledge gaps will ultimately lead to a more complete understanding of the microbe-host interplay in COPD. This will permit clearer distinctions between acute and chronic infections and more granular patient stratification that will enable better management of these features and of COPD.